Eliminating redundancies in cascaded supply chains and its organizational implementation issues - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2000)
The unified demand planning process proposed is an intention to centralize demand planning activities for cascaded supply chain (CSC) partners. It is a collaboration process based on electronic logistics. We concentrate on the demand planning process to illustrate how redundancies occur in CSC, and we suggest the unification of demand planning processes to eliminate redundancies regarding electronic logistics. © 2000 IEEE.